Early immune and host cell responses to Cryptosporidium infection - Mead, Jan R. (Frontiers in Parasitology, 2023)
Cryptosporidium spp. are opportunistic protozoan parasites that infect epithelial cells of the small intestine and cause diarrheal illness in both immunocompetent and immunodeficient individuals. These infections may be more severe in immunocompromised individuals and young children, especially in children under 2 in developing countries. The parasite has a global distribution and is an important cause of childhood diarrhea where it may result in cognitive impairment and growth deficits. Current therapies are limited with nitazoxanide being the only FDA-approved drug. However, it is not efficacious in immunocompromised patients. Additionally, there are no vaccines for cryptosporidiosis available. While acquired immunity is needed to clear Cryptosporidium parasites completely, innate immunity and early responses to infection are important in keeping the infection in check so that adaptive responses have time to develop. Infection is localized to the epithelial cells of the gut. Therefore, host cell defenses are important in the early response to infection and may be triggered through toll receptors or inflammasomes which induce a number of signal pathways, interferons, cytokines, and other immune mediators. Chemokines and chemokine receptors are upregulated which recruit immune cells such neutrophils, NK cells, and macrophages to the infection site to help in host cell defense as well as dendritic cells that are an important bridge between innate and adaptive responses. This review will focus on the host cell responses and the immune responses that are important in the early stages of infection.